The Influence of Physical Activity on University Students’ Career Adaptability: A Chain-Mediated Model - Yanlan Chen; Syed Kamaruzaman Syed Ali; Hutkemri Zulnaidi; Annisaa Basar (SAGE Open)
This study explores the relationship between physical activity and career adaptability among Chinese university students and investigates the underlying mechanisms involved. A survey was conducted with 420 university students using various scales to measure physical activity, motives for physical activity, psychological capital, and career adaptability. The results of the study showed that: (1) physical activity has a positive predictive effect on university students’ career adaptability (β = .0005, 95% CI [0.0002, 0.0008]); (2) physical activity effectiveness and psychological capital play a mediating role in physical activity and university students’ career adaptability, and at the same time, this mediating role contains three paths: the separate mediating role of physical activity effectiveness (β = .0255, 95% CI [0.0046, 0.0509]), the separate mediating role of psychological capital (β = .0804, 95% CI [0.0375, 0.1282]), and the chain mediating role of physical activity effectiveness–psychological capital (β = .0437, 95% CI [0.0224, 0.0675]). Increased physical activity leads to increased physical activity effectiveness, which leads to increased levels of psychological capital, and ultimately to increased levels of career adaptability in university students. This study provides new insights into the career adaptability of university students and provides a reference for their career development.